Artificial Intelligence Algorithms and Generative AI in Education (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This Reprint explores the transformative influence of artificial intelligence (AI) and generative AI on education. It presents a collection of research studies examining how advanced algorithms, adaptive systems, and intelligent tutoring technologies are reshaping teaching, learning, and assessment. The contributions analyze both opportunities and challenges arising from AI integration, highlighting the potential of personalized and data-driven approaches to improve educational outcomes. Ethical considerations, innovative methodologies, and practical implementations are also discussed, offering a comprehensive perspective on how AI can support inclusive and engaging learning environments.